Value-Based Management Education: The Case of Health Care Management Course - Vlado Dimovski; Judita Peterlin; Barbara Grah; Simon Colnar (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
The paper presents educational and teaching change by discussing the results of our study of management education in the health care sector in order to foster innovation for the purpose of better learning, teaching and curriculum development. Personal reflection and content analysis were used as a method to identify health care students' values and perceptions of role models, management and decision-making patterns. Decision-making in health care demands risk management, crisis management, precision and good knowledge of personal abilities and values. Many of our health care students will after the completion of our course work with patients in difficult life situations that will bring with them many ethical dilemmas and emotional pressure. In order to support health care staff in professional decision-making and enable them making the right decisions for the majority of stakeholders (patients, relatives, nursing staff, physicians, etc.) we will provide recommendations for policy makers.
Keywords: I30; M10; M14; 330; empowerment; knowledge management; management education; agility; resilience